2001
DOI: 10.1128/iai.69.3.1483-1487.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Candidate Virulence Genes of Haemophilus ducreyi during Infection of Human Volunteers

Abstract: Haemophilus ducreyi expresses several putative virulence factors in vitro. Isogenic mutant-to-parent comparisons have been performed in a human model of experimental infection to examine whether specific gene products are involved in pathogenesis. Several mutants (momp, ftpA, losB, lst, cdtC, and hhdB) were as virulent as the parent in the human model, suggesting that their gene products did not play a major role in pustule formation. However, we could not exclude the possibility that the gene of interest was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…RT-PCR analysis of RNA prepared from rabbit lesion material confirmed that all three genes of the H. ducreyi cdtABC cluster were transcribed in rabbit skin during infection. In vivo transcription of at least cdtB was also shown to occur in human volunteers infected with wild-type H. ducreyi (48). These findings suggest that the failure to observe diminished virulence with the H. ducreyi cdtA, cdtB, and cdtC mutants in rabbits and with the cdtC mutant in humans is unlikely to be due to a lack of expression of the relevant gene products in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…RT-PCR analysis of RNA prepared from rabbit lesion material confirmed that all three genes of the H. ducreyi cdtABC cluster were transcribed in rabbit skin during infection. In vivo transcription of at least cdtB was also shown to occur in human volunteers infected with wild-type H. ducreyi (48). These findings suggest that the failure to observe diminished virulence with the H. ducreyi cdtA, cdtB, and cdtC mutants in rabbits and with the cdtC mutant in humans is unlikely to be due to a lack of expression of the relevant gene products in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…The larger EDD required for infection in the swine model suggests that H. ducreyi is a less efficient pathogen for pigs than for humans and that the absence of a candidate virulence determinant may have a more pronounced effect in swine than in humans. In the human model, H. ducreyi achieves a density of 10 5 CFU/lesion at the pustular stage, approximately 1 week after inoculation (38). In the swine model, the number of bacteria decreases from 1.7 ϫ 10 4 CFU to 1.7 ϫ 10 3 CFU 48 h after inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils usually kill bacteria by ingesting them or by releasing toxic products such as superoxide radicals and antimicrobial proteins (10). H. ducreyi replicates during the initial stages of experimental infection in humans (3,38), which suggests that the organism escapes both phagocytosis and killing by toxic products of neutrophils. How H. ducreyi evades phagocytic defenses is unclear.…”
mentioning
confidence: 99%
“…One study on pustules (the lesion just prior to the formation of ulcers) in an experimental human infection reported that there were approximately 10 5 CFU per lesion (56). Therefore, it is unclear what the minimum limit of detection is that is needed to accurately detect a reasonable amount of the HgbA released from H. ducreyi or what the number of organisms is that are heme stressed in clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A second immobilized MAb, directed against a separate antigenic epitope, allows the antigen-antibody complex to be concentrated and visually de- (30,56). Therefore, the generation of MAbs to the HgbA protein seemed to be a logical target.…”
Section: Discussionmentioning
confidence: 99%